2007
DOI: 10.1096/fj.06-7990com
|View full text |Cite
|
Sign up to set email alerts
|

Human X‐Box binding protein‐1 confers both estrogen independence and antiestrogen resistance in breast cancer cell lines

Abstract: Human X-box binding protein-1 (XBP1) is an alternatively spliced transcription factor that participates in the unfolded protein response (UPR), a stress-signaling pathway that allows cells to survive the accumulation of unfolded proteins in the endoplasmic reticulum lumen. We have previously demonstrated that XBP1 expression is increased in antiestrogen-resistant breast cancer cell lines and is coexpressed with estrogen receptor alpha (ER) in breast tumors. The purpose of this study is to investigate the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
169
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(186 citation statements)
references
References 66 publications
16
169
0
1
Order By: Relevance
“…Moreover, SPP1 levels change in response to some stimuli that alter the UPR. Analysis of MCF7 breast cancer cells overexpressing XBP-1, a transcription factor that participates in the UPR and confers both estrogen independence and anti-estrogen resistance, revealed that SPP1 was among the genes that were significantly up-regulated (36). In agreement, we found that doxorubicin, similar to other stimuli that alter the UPR, up-regulates SPP1.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, SPP1 levels change in response to some stimuli that alter the UPR. Analysis of MCF7 breast cancer cells overexpressing XBP-1, a transcription factor that participates in the UPR and confers both estrogen independence and anti-estrogen resistance, revealed that SPP1 was among the genes that were significantly up-regulated (36). In agreement, we found that doxorubicin, similar to other stimuli that alter the UPR, up-regulates SPP1.…”
Section: Discussionsupporting
confidence: 80%
“…There is speculation that activation of the UPR may be associated with the development of anti-oestrogen resistance (Fu et al, 2007;Gomez et al, 2007). UPR induction reduces the occurrence of apoptosis in oestrogen-dependent breast cancer cells treated by oestrogen withdrawal, (which clinically correlates with the use of aromatase inhibitors, Fu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Over-expression of XBP-1, another marker of UPR activity, is correlated with resistance to the apoptotic and anti-proliferative effects of antioestrogens, (Davies et al, 2008). The UPR-activated splice variant of XBP-1, (XBP-1s), confers anti-oestrogen resistance and oestrogen-independent growth in breast cancer cell lines in vitro (Gomez et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was reported that XBP1s overexpression leads to increased BCL-2 expression in a breast cancer cell line (19). In a hematopoietic cell line that undergoes apoptosis upon interleukin (IL)-3 withdrawal, overexpression of XBP1s was cytoprotective and attenuated induction of the proapoptotic BCL-2 family member BIM (20).…”
Section: Regulation Of Proliferation Autophagy and Apoptosismentioning
confidence: 99%